2017
DOI: 10.15407/agrisp4.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower (Helianthus annuus L.) productivity under the effect of akm plant growth regulator in the conditions of the southern steppe of Ukraine

Abstract: Aim. The goal of this research was to determine the infl uence of AKM plant growth regulator on the perfor- mance of large-seed Lakomka sunfl ower variety, sowing and yielding properties of seeds. Methods. Agro- chemical and biometric methods. Mathematical analysis of the results was carried out by Student’s test and licensed Agrostat computer program. Results. The results of the study on the impact of AKM plant growth regulator (PGR) on growth, development and yield formation of sunfl ower in low moisture con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Present world consumption of oils is 123.8 million tons and expected to increase to 137 million tons per year in the next decade (ISTA, 2016). Sunflower is the third largest source of vegetable oil worldwide next to soybean and groundnut both in terms of area and production (Yeremenko et al, 2017). In terms of production, the top countries are Ukraine (11.9 million tons), Russia (9.7 mt), European Union (7.72 m t), Argentina (2.7 m t), Turkey (1.1 m t), India (0.52 m t) and others (7.18 million tons) (FAOSTAT, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Present world consumption of oils is 123.8 million tons and expected to increase to 137 million tons per year in the next decade (ISTA, 2016). Sunflower is the third largest source of vegetable oil worldwide next to soybean and groundnut both in terms of area and production (Yeremenko et al, 2017). In terms of production, the top countries are Ukraine (11.9 million tons), Russia (9.7 mt), European Union (7.72 m t), Argentina (2.7 m t), Turkey (1.1 m t), India (0.52 m t) and others (7.18 million tons) (FAOSTAT, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yeremenko et al found that, although both hybrid and plant growth promoters affect yield of sunflower. They found influence of hybrid (85%) is much much more than the PGR (7.5%) [29]. Naik et al [30] observed the effect of 2,4-Dichlorophenoxyacetic acid and its lanthanide complexes, and indole 3 acetic acid-derived Schiff base and their lanthanide complexes on the germination and growth activity on wheat seeds, and found the best results at 10 -6 M concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced phosphorous nutrition reduces the water consumption coefficient of sunflower plants (Yeremenko et al, 2017;Buldykova, Sheudzhen & Bondareva, 2015).…”
Section: Introductionmentioning
confidence: 99%